2011
DOI: 10.1088/2041-8205/733/2/l18
|View full text |Cite
|
Sign up to set email alerts
|

Global Simulations of the Magnetic Field Evolution in Barred Galaxies Under the Influence of the Cosmic-Ray-Driven Dynamo

Abstract: We present three-dimensional global numerical simulations of the cosmic-ray (CR) driven dynamo in barred galaxies. We study the evolution of the interstellar medium of the barred galaxy in the presence of non-axisymmetric component of the potential, i.e. the bar. The magnetohydrodynamical dynamo is driven by CRs, which are continuously supplied to the disk by supernova (SN) remnants. No magnetic field is present at the beginning of simulations but one-tenth of SN explosions is a source of a small-scale randoml… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
38
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 17 publications
9
38
0
Order By: Relevance
“…The larger the SNR, the faster the growth rate, but excessive supernova activity can suppress the dynamo action. Hanasz et al (2009b) demonstrated cosmic-ray-driven dynamo action via global disk spiral galaxies, and Kulpa-Dybeł et al (2011) confirmed the result for barred galaxies. They found that the azimuthal magnetic flux grows on a time-scale of about 270 Myr.…”
Section: Introductionsupporting
confidence: 60%
“…The larger the SNR, the faster the growth rate, but excessive supernova activity can suppress the dynamo action. Hanasz et al (2009b) demonstrated cosmic-ray-driven dynamo action via global disk spiral galaxies, and Kulpa-Dybeł et al (2011) confirmed the result for barred galaxies. They found that the azimuthal magnetic flux grows on a time-scale of about 270 Myr.…”
Section: Introductionsupporting
confidence: 60%
“…We made similar kinematical and dynamical assumptions to those in Kulpa-Dybeł et al (2011). The CR-driven dynamo models of a barred galaxy were solved numerically in a 3D computational box with the size of L x = L y = 30 kpc and L z = 7 kpc.…”
Section: Galactic Disk Modelmentioning
confidence: 99%
“…Next, a star can explode as an SN, releasing magnetized material that spreads into the ISM. Rees (1987) suggested that Crab-type SNe remnants have fields of the order of 10 −4 G. He also estimated that at an early stage in galactic evolution there could have been as much as 10 6 randomly oriented SNe remnants similar to the Crab Nebula, giving rise to quite substantial seed fields of the order of 10 −9 G. The recent simulations by Hanasz et al (2009b) and Kulpa-Dybeł et al (2011) have shown that small-scale magnetic fields of stellar origin can be amplified exponentially by the CR driven dynamo up to the observed values, which means that SNe explosions can produce a sufficiently strong seed field for the CR dynamo action. Dubois & Teyssier (2010) did 3D MHD calculations of an isolated dwarf galaxy that had been formed self-consistently inside a cooling halo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter type of model is much less demanding of computing resources, and readily allows extensive exploration of parameter space, and also the study of phenomena such as large-scale gas streaming in A&A 566, A40 (2014) barred galaxies (e.g. Moss 1998;Moss et al 1998Moss et al , 2001Moss et al , 2007Kulpa-Dybel et al 2011;Kim & Stone 2012), and the effects of spiral arms on dynamo action (Shukurov 1998;Moss 1998;Moss et al 1998Chamandy et al 2013a,b). There are also many studies of the effects of externally driven gas flows on the gas content of galaxies (e.g.…”
Section: Introductionmentioning
confidence: 99%